The Selah Pilot Study of Spiritual, Mindfulness, and Stress Inoculation Practices on Stress-Related Outcomes Among United Methodist Clergy in the United States - Proeschold-Bell, Rae Jean (Journal of religion and health, 2023)
The job-demand-control-support model indicates that clergy are at high risk for chronic stress and adverse health outcomes. A multi-group pre-test-post-test design was used to evaluate the feasibility, acceptability, and range of outcome effect sizes for four potentially stress-reducing interventions: stress inoculation training, mindfulness-based stress reduction (MBSR), the Daily Examen, and Centering Prayer. All United Methodist clergy in North Carolina were eligible and recruited via email to attend their preferred intervention. Surveys at 0, 3, and 12 weeks assessed symptoms of stress, anxiety, and perceived stress reactivity. Heart rate variability (HRV) was assessed at baseline and 12 weeks using 24 h ambulatory heart rate monitoring data. A subset of participants completed in-depth interviews and reported skill practice using daily text messages. Standardized mean differences with 95% and 75% confidence intervals were calculated for the change observed in each intervention from baseline to 3 and 12 weeks post-baseline to determine the range of effect sizes likely to be observed in a definitive trial. 71 clergy participated in an intervention. The daily percentage of participants engaging in stress management practices ranged from 47% (MBSR) to 69% (Examen). Results suggest that participation in Daily Examen, stress inoculation, or MBSR interventions could plausibly result in improvement in stress and anxiety at 12 weeks with small-to-large effect sizes. Small effect sizes on change in HRV were plausible for MBSR and Centering Prayer from baseline to 12 weeks. All four interventions were feasible and acceptable, although Centering Prayer had lower enrollment and mixed results.